Exploring the willingness toward HIV immediate test and treat among MSM in Nairobi and its environs: a cross-sectional study - Ndungu, Kingori; Gichangi, Peter; Temmerman, Marleen (Frontiers in Public Health, 2024)
Background In the test and treat initiative, high-risk populations are screened for human immunodeficiency virus (HIV) infection and start early treatment if diagnosed positive. This study explores factors associated with willingness to initiate testing and immediate treatment among men who have sex with men (MSM) in Nairobi and its environs. The study was informed by a conceptual framework combining the AIDS Risk Reduction Model (ARRM) and the Modified Social Ecological Model. Methods This cross-sectional exploratory study targeted MSM (aged 18–60 years) reporting active engagement in anal or oral sex with men in Nairobi and its surrounding areas. Purposive sampling was used to identify data collection sites, and then snowballing was employed to reach the respondents. Data analysis was performed using SPSS version 23, and binary logistics regression was used for inferential analysis. Results Between July 2018 and June 2019, 391 MSM were recruited to fill out a self-administered questionnaire, out of which 345 complete questionnaires were analyzed. Never been tested for HIV, private/NGO as the facility of the last HIV test, and had unprotected anal sex were listed as the reasons for taking the most recent test, and the results of the most recent HIV test and seeking a post self-test confirmation were associated with a higher likelihood of accepting the immediate HIV test and treat initiative. Additionally, a preference for a health provider as the first source of support, belief in the efficacy of ARVs, and disclosure about being on ART were the other reasons. Additionally, being aged 25+ years, having more than 60 USD monthly income, and having inconsistent condom use during sex were associated with a higher likelihood of accepting the immediate HIV test and treat initiative. Barriers to the immediate test and treat strategy included stigma from healthcare providers and concerns about disruptions in lifestyle through antiretroviral therapy (ART) use. Conclusion Interventions aimed at increasing the HIV test and treat initiative in Kenya may need to take into account the demographic and social characteristics of MSM, including age, lack of habitual HIV testing, and lifestyle changes before and upon enrollment in ART. Projects should also consider working closely with healthcare facilities to strengthen treatment preparation, especially for asymptomatic MSM and those who may not be immediately willing to choose the test and treat strategy.